2011
DOI: 10.2341/10-315-l
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Premolar Cuspal Deflection in Bulk or in Incremental Composite Restoration Methods

Abstract: SUMMARY Objectives This study examined the cuspal deflection of maxillary premolars when either a bulk filling or incremental filling technique was employed using a range of composites with different elastic moduli. Methods Four brands of composite materials, Heliomolar (HM, Ivoclar Vivadent, Schaan, Liechtenstein), Heliomolar HB (HH, Ivoclar Vivadent, Schaan, Liechtenstein), Filtec Supreme X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…In a study conducted by Kim ME and Park SH, it was concluded that the incremental filling techniques reduced the amount of cuspal deflection when compared to bulkfill technique [21]. In the current study, the overall amount of cusp deflection of the incrementally filled groups (Group II and Group III) was significantly lesser than that of bulk filled group (Group I) (p<0.05) hence, supporting the previous studies [3,6].…”
Section: Sample Measurementsupporting
confidence: 81%
See 1 more Smart Citation
“…In a study conducted by Kim ME and Park SH, it was concluded that the incremental filling techniques reduced the amount of cuspal deflection when compared to bulkfill technique [21]. In the current study, the overall amount of cusp deflection of the incrementally filled groups (Group II and Group III) was significantly lesser than that of bulk filled group (Group I) (p<0.05) hence, supporting the previous studies [3,6].…”
Section: Sample Measurementsupporting
confidence: 81%
“…The incremental insertion technique has been documented to decrease the polymerization shrinkage by reducing the bulk of composite cured with each layer [21,22]. Decreasing the C-factor has also been suggested to reduce the curing shrinkage by permitting unobstructed ''flow''of the material in the unbonded surface layer [3].…”
Section: Sample Measurementmentioning
confidence: 99%
“…Some investigators have studied the direct effect of polymerization contraction on cuspal flexure of mesialocclusal-distal cavity preparations, showing greater flexure when composites are very well cured using bulk-cure vs. incremental placement techniques [75][76][77], and reduced flexure when certain flexible liners are placed [78]. A criticism of some of these studies is the amount of illumination time used to ensure complete cure of the composite, which would be considered to be excessive clinically, and leading to unrealistically high extents of cure that produce greater contraction stress and more deleterious effects.…”
Section: Polymerization Stress -In Vitro Evidencementioning
confidence: 99%
“…The energy of the light emitted from a light curing unit decreases drastically when transmitted through a resin composite, leading to a gradual decrease in the DC of the resin composite [14]. Thus far, an incremental layering technique has been the standard to sufficiently convert monomers [15]. Typically, this technique consists of placing increments of resin composite material, in a thickness of 2 mm or less, followed by exposure to light curing, and then repeating the increments until the preparation is filled [16].…”
Section: Introductionmentioning
confidence: 99%